2017
DOI: 10.1371/journal.pgen.1006756
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Native American ancestry and leading causes of death: Mapuche ancestry-specific associations with gallbladder cancer risk in Chile

Abstract: Latin Americans are highly heterogeneous regarding the type of Native American ancestry. Consideration of specific associations with common diseases may lead to substantial advances in unraveling of disease etiology and disease prevention.Here we investigate possible associations between the type of Native American ancestry and leading causes of death. After an aggregate-data study based on genome-wide genotype data from 1805 admixed Chileans and 639,789 deaths, we validate an identified association with gallb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…Mapuche Native American ancestry has been strongly associated with the risk of GBC, and we found that the percentage of Mapuche Native American ancestry of the male donor of the primary tumor cells was 36%. For comparison, the first (third) quartiles of Mapuche ancestry reported in a recent study that included 1805 Chileans were 28% (43%) [6], confirming the representativeness of the established GBC cell lines for the Chilean population. The three new cell lines displayed an epithelial phenotype and showed abnormality in structure and number of chromosomes, with a tendency to triploidy.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Mapuche Native American ancestry has been strongly associated with the risk of GBC, and we found that the percentage of Mapuche Native American ancestry of the male donor of the primary tumor cells was 36%. For comparison, the first (third) quartiles of Mapuche ancestry reported in a recent study that included 1805 Chileans were 28% (43%) [6], confirming the representativeness of the established GBC cell lines for the Chilean population. The three new cell lines displayed an epithelial phenotype and showed abnormality in structure and number of chromosomes, with a tendency to triploidy.…”
Section: Discussionsupporting
confidence: 58%
“…Surrogates of African and European ancestry were 87 Yorubans in Ibadan, Nigeria, and 80 Utah residents with Northern and Western European ancestry from the 1000 Genome Project. Nine Mapuche and nine Aymara individuals were selected to represent the two largest indigenous peoples in Chile based on the three following criteria: four grandparental Mapuche or Aymara surnames, estimated Native American proportion of at least 74% for Mapuche and at least 99% for Aymara reference individuals, and mitochondrial DNA haplogroups consistent with Mapuche (haplogroup C or D) or Aymara (haplogroup B) descent [6]. The ADMIXTURE software was used for supervised estimation of the African, European, Mapuche Native American and Aymara Native American ancestry components relying on the above-mentioned identified common variants, reference individuals and genotype data from a recent study that included 1805 Chileans [6,97].…”
Section: Variant and Gene Expression Analysis From Rna Sequencing Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Hispanic populations of New Mexico also show an elevated incidence of GBC (compared to Caucasians in New Mexico), though not to the degree seen in Native Americans [ 4 ]. In Chile, for each 1% increase in Mapuche heritage, an indigenous people common in Chile, there is an associated 3.7% increase in risk for GBC [ 9 ]. These observations argue for specific predisposing genetic factors (direct or indirect) unique to certain indigenous populations.…”
Section: Epidemiology and Risk Factors For Gallbladder Cancermentioning
confidence: 99%
“…Studies into genetic conditions common to South American nations tend to be underrepresented in the literature which is historically European-centric ( Carvajal-Carmona et al, 2000 , 2003 ; Bedoya et al, 2006 ; Criollo-Rayo et al, 2018 ). Recently Lorenzo Bermejo et al (2017) showed that the percentage of indigenous ancestry in modern Chileans is correlated with an increased risk of developing gall bladder cancer ( Lorenzo Bermejo et al, 2017 ). Investigations into population structure form the basis of these studies, and several large recent studies have begun to shed light upon the genetic ancestry of modern South American populations.…”
Section: Introductionmentioning
confidence: 99%